The relationship between information literacy and digital self-efficacy in teaching information literacy for new teachers in Lithuania - Palmira Pečiuliauskienė (Social Sciences and Humanities Open)
This study aims to reveal the role of different components of information literacy (e.g. information search and evaluation, information processing and dissemination) in beginner teachers’ digital self-efficacy in teaching information literacy. Undergraduate students and requalification programme teachers from two Lithuanian teacher training universities took part in the study. Confirmatory factor analysis and latent multi-group structural equation modelling revealed the statistically significant effects of all information literacy components on digital self-efficacy in the teaching of information literacy both groups of teachers. The quantitative data analysis showed that two components of information literacy—perceived information evaluation and information processing ability—had a strong direct impact on digital self-efficacy in both groups of respondents. This finding may help to support the improvement of teacher training and professional development programmes, with a focus on teaching information literacy.